Resource allocation for downlink coordinated multipoint (CoMP) in lte-advanced - Katiran, Norshidah (2015)
Coordinated multipoint (CoMP) in LTE-Advanced is considered as a promising way to enhance spectrum efficiency in interference-limited wireless network through base station (BS) cooperation. However, resource allocation is one of the key challenges faced by CoMP network because resource allocation strategy of one cell affects the other cells’ performance. Moreover, due to the scarcity of wireless network resources such as bandwidth and power, efficient resource allocation strategy is always desirable. In this paper, a low-complexity resource allocation strategy in CoMP that aims to achieve high network throughput is presented. The resource allocation strategy consists of three modules which are performed sequentially; user allocation module, subcarrier allocation module and power allocation module. Our simulation study shows that the proposed strategy gives significant performance gain in CoMP LTE-Advanced network.